At-Risk Testing for Pompe Disease Using Dried Blood Spots: Lessons Learned for Newborn Screening - Zoltan Lukacs; Petra Oliva; Paulina Nieves Cobos; Jacob Scott; Thomas P. Mechtler; David C. Kasper (MDPI AG, 2020)
Pompe disease (GSD II) is an autosomal recessive disorder caused by deficiency of the lysosomal enzyme acid-α-glucosidase (GAA, EC 3.2.1.20), leading to generalized accumulation of lysosomal glycogen especially in the heart, skeletal, and smooth muscle, and the nervous system. It is generally classified based on the age of onset as infantile (IOPD) presenting during the first year of life, and late onset (LOPD) when it presents afterwards. In our study, a cohort of 13,627 samples were tested between January 2017 and December 2018 for acid-α-glucosidase (GAA, EC 3.2.1.20) deficiency either by fluorometry or tandem mass spectrometry (MS). Testing was performed for patients who displayed conditions of unknown etiology, e.g., CK elevations or cardiomyopathy, in the case of infantile patients. On average 8% of samples showed activity below the reference range and were further assessed by another enzyme activity measurement or molecular genetic analysis. Pre-analytical conditions, like proper drying, greatly affect enzyme activity, and should be assessed with measurement of reference enzyme(s). In conclusion, at-risk testing can provide a good first step for the future introduction of newborn screening for Pompe disease. It yields immediate benefits for the patients regarding the availability and timeliness of the diagnosis. In addition, the laboratory can introduce the required methodology and gain insights in the evaluation of results in a lower throughput environment. Finally, awareness of such a rare condition is increased tremendously among local physicians which can aid in the introduction newborn screening.